The Effects of Flipped Classroom on Learning Performance in Management Courses at Vocational and Technical Colleges in China - Wanmei, Wang (Universiti Malayia Sarawak, 2025)
This study examined the effects of the flipped classroom approach on learning performance among first-year management students in five vocational and technical colleges in Anhui Province, China. A mixed-methods quasi-experimental design was employed, integrating both quantitative and qualitative approaches. During a six-week teaching experiment, 50 classes comprising 1,000 students were randomly assigned to experimental and control groups. The experimental group adopted the flipped classroom model, while the control group followed traditional teaching approaches. The primary objective was to assess the flipped classroom's effects in enhancing learning performance, including academic achievement, successful intelligence, and learning attitudes. The research framework identified the independent variables as the flipped classroom and traditional classroom approaches, as well as demographic profiles (such as college and gender). The dependent variable was learning performance, with cognitive style serving as a moderating variable. Control variables included grade level, teaching focus, and teaching materials. The experimental results showed that the flipped classroom significantly outperformed the traditional classroom. Flipped students had a 41.642-point increase in academic achievement test scores compared to 30.998 points for traditional students. Successful intelligence scores rose by 9.146 points in the flipped group and decreased by 0.07 points in the traditional group. Learning attitudes improved by 33.092 points in the flipped group, compared to a 0.394-point decrease in the traditional group. Findings indicated that the flipped classroom model significantly improved academic achievements, successful intelligence, and fostered a more positive learning attitude compared to traditional teaching methods. However, cognitive style did not moderate the effects of the flipped classroom approach. This study provided empirical evidence on the effects of the flipped classroom in China's Vocational and Technical Colleges (VTCs), while explored the moderating role of cognitive styles to deepen the understanding of how different teaching methods impact learning performance. It contributed to the broader discussion on personalized and student-centered learning approaches in China's Vocational and Technical Education (VTE). Future research could expand by diversifying samples, conducting longitudinal studies, incorporating additional variables (e.g., self-efficacy, learning motivation), and exploring cross-disciplinary contexts. Keywords: Flipped Classroom, Vocational and Technical Colleges, Learning Performance, Cognitive Styles